2017
DOI: 10.1016/j.socscimed.2017.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Opioid pharmacovigilance: A clinical-social history of the changes in opioid prescribing for patients with co-occurring chronic non-cancer pain and substance use

Abstract: There is growing concern among US-based clinicians, patients, policy makers, and in the media about the personal and community health risks associated with opioids. Perceptions about the efficacy and appropriateness of opioids for the management of chronic non-cancer pain (CNCP) have dramatically transformed in recent decades. Yet, there is very little social scientific research identifying the factors that have informed this transformation from the perspectives of prescribing clinicians. As part of an on-goin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Payment models that reimburse for the time necessary for CNCP assessment would help to alleviate time pressure as a barrier to adequate and appropriate pain management. As changes are implemented, 29 caution is needed in addressing the ways in which the time demands of new policies impact care for socially vulnerable, medically complex patients in safety-net settings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Payment models that reimburse for the time necessary for CNCP assessment would help to alleviate time pressure as a barrier to adequate and appropriate pain management. As changes are implemented, 29 caution is needed in addressing the ways in which the time demands of new policies impact care for socially vulnerable, medically complex patients in safety-net settings.…”
Section: Resultsmentioning
confidence: 99%
“…It suggests that although it is well known that time is a challenge in primary care generally, the specific implications of time pressure for patterns of opioid prescribing and discontinuation should be examined as prescribing norms shift. 29 Research has shown that recommended practices can support clinicians in their efforts to manage opioid-related risks. 23,30 Clinicians felt that new strategies were needed to increase the time available for CNCP and opioid management and improve the quality of care for medically complex patients with CNCP and substance use who are already receiving opioids.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study by Knight et al ., many physicians reported that their initial opioid prescribing practices (before the era of pharmacovigilance) were related to concerns regarding the inequality of pain treatment for marginalized groups of patients. Laws and regulations cause clinicians to experience moral distress related to the conflict between providing “appropriate pain management for individual patients” and “subjecting patients or the community to iatrogenic harm.” This concern has long been voiced with regard to the prescribing caps stipulated in regulations and laws regarding opioid prescription doses and duration. To many physicians, the withdrawal of care from chronic pain patients who have been stable on opioids constitutes inhumane treatment .…”
Section: Recommendationsmentioning
confidence: 99%
“…The overprescribing of opioids led to increased tolerance and iatrogenic addiction, which subsequently drove trends in illicit opioid use and abuse. By 2011, according to the clinical social history provided by medical anthropologist Kelly Knight and coauthors, the pendulum for opioid prescribing then swung in the other direction, ushering in an era of “increased prescription surveillance” or “opioid pharmacovigilance” in which policies designed to reduce opioid prescribing, such as mandatory prescription guidelines and prescription monitoring programs (PMPs), were put in place . New educational programs focused on safe prescribing practices were tied to these surveillance efforts.…”
mentioning
confidence: 99%
“…Patients receiving care in safety-net settings report high burdens of pain and experience barriers to accessing treatments. 1,8,9 Consensus guidelines call for improving the availability of multimodal or multidisciplinary pain treatments, defined as programs that combine traditional medical therapy (procedural and/or medications), with nonpharmacologic approaches such as behavioral therapies, physical movement or rehabilitation, and complementary and alternative medicine approaches. [10][11][12][13] San Francisco County has high rates of opioid overdose, with deaths clustering in areas of the city with a concentration of low-income housing.…”
Section: Introductionmentioning
confidence: 99%